2019
DOI: 10.3390/rs12010022
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Analysis of Photogrammetric UAV Image Blocks—Influence of Camera Calibration Error

Abstract: Unmanned aerial vehicles (UAV) are increasingly used for topographic mapping. The camera calibration for UAV image blocks can be performed a priori or during the bundle block adjustment (self-calibration). For an area of interest with flat scene and corridor configuration, the focal length of camera is highly correlated with the height of the camera. Furthermore, systematic errors of camera calibration accumulate on the longer dimension and cause deformation. Therefore, special precautions must be taken when e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Strengths comes from a dense and homogenous block control, as all camera stations are measured. Weaknesses are the risks that inaccurate inner orientation parameters may affect tie points ground coordinates (Zhou et al, 2020). Unlike nadiral blocks with GCP, where with dense enough ground control these errors are to some extent adsorbed by exterior orientation parameters, if block control is limited to camera stations the ground coordinates are not effectively shielded.…”
Section: Uav Surveys In Mountain Areasmentioning
confidence: 99%
“…Strengths comes from a dense and homogenous block control, as all camera stations are measured. Weaknesses are the risks that inaccurate inner orientation parameters may affect tie points ground coordinates (Zhou et al, 2020). Unlike nadiral blocks with GCP, where with dense enough ground control these errors are to some extent adsorbed by exterior orientation parameters, if block control is limited to camera stations the ground coordinates are not effectively shielded.…”
Section: Uav Surveys In Mountain Areasmentioning
confidence: 99%
“…Shatangju tree. With the development of UAV technology, UAV images have also been widely used [49][50][51][52][53][54][55][56]. Studies [10][11][12][13] have shown that UAV tilt photogrammetry can quickly and conveniently obtain images and texture information of forests, pine trees, eucalyptus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the impact analysis of different camera parameters, the capability of LiDAR to provide control information for decoupling the involved IOPs is evaluated. Although the impact of an erroneous/gradually varying principal distance and rolling shutter effect on the accuracy of 3D reconstruction has been experimentally investigated by Zhou et al [41], this section will focus on analytically and experimentally analyzing the impact of the principal distance and distortion parameters.…”
Section: Bias Impact Analysis For Camera Iopsmentioning
confidence: 99%